A Review on the Stability, Sustainability, Storage and Rejuvenation of Aerobic Granular Sludge for Wastewater Treatment - Shameem, K. S.; Sabumon, P. C. (Water (Basel), 2023)
Aerobic granular sludge (AGS) is a recent innovative technology and is considered a forthcoming biological process for sustainable wastewater treatment. AGS is composed of the dense microbial consortium of aerobic, anaerobic, and facultative types of bacteria. The mechanism of AGS formation and its stability for long-term operation is still a subject of current research. On the other hand, AGS makes the treatment process sustainable in a cost-effective way. However, in order for AGS to be applied in a broader range of applications, there are several challenges to overcome, such as slow-speed granulation and the disintegration of AGS after granulation. Many factors play a role in the stability of granules. The storage of granules and the later use of them for granulation startup is a feasible method for reducing the time for granulation and maintaining stability. This review focuses on the granulation process and characteristics of AGS, granulation time and the stability of AGS under different conditions, the comparison of different storage methods of granules, and their recovery and rejuvenation. From this review, it is evident that additional research is required to assess the effectiveness of regenerated AGS after prolonged storage to promote AGS technology for commercial applications.